2021
DOI: 10.1016/s2468-2667(20)30261-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of a health systems intervention for latent tuberculosis infection management (ACT4): a cluster-randomised trial

Abstract: Background Reaching the UN General Assembly High-Level Meeting on Tuberculosis target of providing tuberculosis preventive treatment to at least 30 million people by 2022, including 4 million children under the age of 5 years and 20 million other household contacts, will require major efforts to strengthen health systems. The aim of this study was to evaluate the effectiveness and cost-effectiveness of a health systems intervention to strengthen management for latent tuberculosis infection (LTBI) in household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Engaging community health workers may support this effort; Zawedde-Muyanja et al found improvements in screening of household contacts and initiation and completion of TPT among children in Uganda following training of community health workers [25] . Economic analysis of a multi-country (Benin, Canada, Ghana, Indonesia, and Vietnam) trial to strengthen management of household contacts of people with confirmed TB estimated a cost of the intervention and TPT-associated clinical care of CA$1348 per contact [26] . Investigators working in Vietnam calculated an incremental cost-effectiveness ratio of $544 per disability-adjusted life year averted for a serial screening program among household contacts of adults with smear-positive TB [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Engaging community health workers may support this effort; Zawedde-Muyanja et al found improvements in screening of household contacts and initiation and completion of TPT among children in Uganda following training of community health workers [25] . Economic analysis of a multi-country (Benin, Canada, Ghana, Indonesia, and Vietnam) trial to strengthen management of household contacts of people with confirmed TB estimated a cost of the intervention and TPT-associated clinical care of CA$1348 per contact [26] . Investigators working in Vietnam calculated an incremental cost-effectiveness ratio of $544 per disability-adjusted life year averted for a serial screening program among household contacts of adults with smear-positive TB [27] .…”
Section: Discussionmentioning
confidence: 99%
“…We are interested in detecting a difference between the proportion of HHC starting TPT in those randomized to the standard algorithm and each of the alternative regimens. The proportion starting TPT during phase 2 of ACT4 [ 26 , 27 ], at the same study sites, when solutions had been implemented and the barriers of TST and CXR had been resolved, will be used as the likely proportion in the standard arm. We consider that accepting to start treatment will likely be strongly influenced by other household members.…”
Section: Methods and Analysismentioning
confidence: 99%
“…This gave an intra-class correlation coefficient (ICC) or clustering effect of HHC of 0.33. Based on this ICC and an average of three HHC aged 5–50 years (observed in the ACT4 trial) [ 26 , 27 ], we can estimate the design effect as 1 + (household size-1)*ICC. We will assess differences across sites but expect randomization to reduce potential confounders.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations